A foundation course in human values and professional ethics : presenting a universal approach to value education through self-exploration - Gaur, R.R.; Sangal, R.; Bangaria, G.P. (New Delhi : Excel books, 2010)
This textbook, designed for a foundation course on Human Values and Professional Ethics, is an outcome of the long-drawn search, visualization and extensive experimentation by the authors and their colleagues towards evolving an effective and universally acceptable methodology for introducing value education in the present curricula of technical and other professional institutions.
Includes glossary and references.
Keywords: Values -- Textbooks; Professional ethics -- Textbooks; Professional ethics